Effect of mobile service quality to e-trust to develop e-satisfaction and e-loyalty mobile banking services - Suariedewi, I Gusti Agung Ayu Mas; Suprapti, Ni Wayan Sri (International research journal of management, IT and social sciences, 2020)
The development of information and communication technology has caused enormous changes in the business. To win the competition by reaching more and more customers, the bank must innovate in providing services that are in accordance with customer demands. One way is to offer mobile banking (m-banking). Trust is one of the important factors that influence consumers in dealing with m-banking. This study aims to explain the effect of mobile service quality on e-trust, e-satisfaction, and e-loyalty of mobile banking (m-banking) users. The respondents of this study are M-BCA, Mandiri Online or BRI Mobile users. Data was collected using a questionnaire from 120 respondents in Denpasar City and using m-banking at least 2 times a month. Data is processed using SEM-PLS analysis techniques with the Smart PLS application version 3.0. The results of the study found that mobile service quality has a positive and significant effect on e-trust. E-trust has a positive and significant effect on e-satisfaction, e-satisfaction has a positive and significant effect on e-loyalty and E-trust has a positive and significant effect on e-loyalty. Theoretical implications in this study are to enrich empirical evidence of research related to mobile service quality, e-trust, e-satisfaction and e-loyalty.